Soil nifH-harboring community assemblage varies across pecan cultivars - Liu, Junping; Wang, Hankun; Tang, Yujie; Bao, Jiashu; Tan, Pengpeng; Peng, Fangren (Frontiers in Microbiology, 2026)
IntroductionThis study focused on three pecan (Carya illinoinensis) cultivars (‘Pawnee’, ‘Mahan’, and ‘Jinhua’), systematically assessing variations in soil nitrogenase activity, characteristics traits of nifH-harboring microbial communities across these cultivars.MethodsUsing high-throughput sequencing technology, differences in the diversity, community composition, and network structure of nifH-harboring communities in the rhizosphere and bulk soils of pecan were examined across cultivars.ResultsBoth cultivar type and soil compartment had significant effects on nitrogenase activity (p < 0.01). Among the three cultivars, ‘Mahan’ exhibited the highest soil nitrogenase activity in both its rhizosphere and bulk soils relative to the other two cultivars. Notably, rhizosphere soils across all cultivars displayed significantly stronger soil nitrogenase activity than their bulk soil counterparts. ‘Mahan’ harbored significantly higher microbial α-diversity (Sobs, Shannon, and Chao indices) than other cultivars (p < 0.05). β-diversity analysis revealed marked community divergence among cultivars, with the most pronounced differences observed in bulk soils. Specifically, the bulk soil of ‘Jinhua’ harbored a distinct microbial signature, marked by significant enrichment of Cyanobacteria and depletion of Alphaproteobacteria. Linear discriminant analysis effect size (LEfSe) further identified Rhizobiales and Burkholderiales as distinct biomarkers for the rhizosphere and bulk soils of ‘Jinhua’, respectively (LDA score > 4.0, p < 0.05). Microbial co-occurrence network analysis showed that the bulk soil of ‘Jinhua’ harbored the most complex microbial interaction network, characterized by the highest number of edges, and average connectivity. In co-occurrence networks, Azohydromonas, Bradyrhizobium, Azoarcus, Rhodomicrobium were found as the keystone taxa in maintaining network stability.DiscussionThis research elucidates the regulatory roles of pecan cultivars in shaping soil nitrogen fixation functions and microbial community assembly, providing valuable practical implications for precision microbiome management in pecan production.